Satellite detection, long‐range transport, and air quality impacts of volcanic sulfur dioxide from the 2014–2015 flood lava eruption at Bárðarbunga (Iceland). Issue 18 (23rd September 2015) - Schmidt, Anja; Leadbetter, Susan; Theys, Nicolas; Carboni, Elisa; Witham, Claire S.; Stevenson, John A.; Birch, Cathryn E.; Thordarson, Thorvaldur; Turnock, Steven; Barsotti, Sara; Delaney, Lin; Feng, Wuhu; et al.
Abstract: The 2014–2015 Bárðarbunga‐Veiðivötn fissure eruption at Holuhraun produced about 1.5 km 3 of lava, making it the largest eruption in Iceland in more than 200 years. Over the course of the eruption, daily volcanic sulfur dioxide (SO2 ) emissions exceeded daily SO2 emissions from all anthropogenic sources in Europe in 2010 by at least a factor of 3. We present surface air quality observations from across Northern Europe together with satellite remote sensing data and model simulations of volcanic SO2 for September 2014. We show that volcanic SO2 was transported in the lowermost troposphere over long distances and detected by air quality monitoring stations up to 2750 km away from the source. Using retrievals from the Ozone Monitoring Instrument (OMI) and the Infrared Atmospheric Sounding Interferometer (IASI), we calculate an average daily SO2 mass burden of 99 ± 49 kilotons (kt) of SO2 from OMI and 61 ± 18 kt of SO2 from IASI for September 2014. This volcanic burden is at least a factor of 2 greater than the average SO2 mass burden between 2007 and 2009 due to anthropogenic emissions from the whole of Europe. Combining the observational data with model simulations using the United Kingdom Met Office's Numerical Atmospheric‐dispersion Modelling Environment model, we are able to constrain SO2 emission rates to up to 120 kilotons per day (kt/d) during early September 2014, followed by a decrease to 20–60 kt/d between 6 and 22 September 2014, followed by a renewed increase to 60–120 kt/d until the end of September 2014. Based on these fluxes, we estimate that the eruption emitted a total of 2.0 ± 0.6 Tg of SO2 during September 2014, in good agreement with ground‐based remote sensing and petrological estimates. Although satellite‐derived and model‐simulated vertical column densities of SO2 agree well, the model simulations are biased low by up to a factor of 8 when compared to surface observations of volcanic SO2 on 6–7 September 2014 in Ireland. These biases are mainly due to relatively small horizontal and vertical positional errors in the simulations of the volcanic plume occurring over transport distances of thousands of kilometers. Although the volcanic air pollution episodes were transient and lava‐dominated volcanic eruptions are sporadic events, the observations suggest that (i) during an eruption, volcanic SO2 measurements should be assimilated for near real‐time air quality forecasting and (ii) existing air quality monitoring networks should be retained or extended to monitor SO2 and other volcanic pollutants. Key Points: The 2014–2015 Icelandic fissure eruption at Bárðarbunga affected air quality in far field Satellite‐derived average daily SO2 burden of 99 ± 49 kt (OMI) and 61 ± 18 kt (IASI) in September 2014 We calculate a total release of 2.0 ± 0.6 Tg of SO2 for September 2014 and fluxes up to 120 kt/d